2016
DOI: 10.5294/laclil.2016.9.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Using Online Translators in the Second Language Classroom: Ideas for Advancedlevel Spanish

Abstract: In this paper, we discuss the benefits of using online translators in the foreign language classroom. Specifically, we discuss how faulty online translator output can be used to create activities that help raise metalinguistic awareness of second language grammar and of the differences between grammatical constructions in the first and second language, which can help with the language learning process. Specific structures for advanced-level Spanish that produce faulty online translator output are explained, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…In addition, educators might implement some of the translation activities suggested in previous research (see Correa, ; Enkin & Mejías‐Bikandi, ; Jiménez‐Crespo, ) and think carefully about the role of translation as a pedagogical tool that can heighten learners’ awareness of the flexibility of language and the subtleties that are involved in precisely conveying one's intended message. Pedagogical activities, such as translating a popular song from English into the target language and then comparing students’ version with GT's, can emphasize the fact that translations are rarely verbatim reproductions of the original text and that the act of translating does not simply involve substituting words in one language for those in another.…”
Section: Discussion and Pedagogical Implicationsmentioning
confidence: 99%
“…In addition, educators might implement some of the translation activities suggested in previous research (see Correa, ; Enkin & Mejías‐Bikandi, ; Jiménez‐Crespo, ) and think carefully about the role of translation as a pedagogical tool that can heighten learners’ awareness of the flexibility of language and the subtleties that are involved in precisely conveying one's intended message. Pedagogical activities, such as translating a popular song from English into the target language and then comparing students’ version with GT's, can emphasize the fact that translations are rarely verbatim reproductions of the original text and that the act of translating does not simply involve substituting words in one language for those in another.…”
Section: Discussion and Pedagogical Implicationsmentioning
confidence: 99%
“…When the English texts were compared and analyzed using online computational assessments, MT English texts were evaluated to be higher in quality in grammar, spelling, and word choice leading the author to conclude that MT can indeed provide effective support in EFL writing. In fact, educational activities such as analyzing mistranslations, preediting, and post-editing were found to help develop meta-linguistic awareness by directing students' attention to the differences and similarities between their native language and their L2 (Abraham, 2009;Correa, 2014;Enkin & Mejías-Bikandi, 2016;Niño, 2009;Somers, 2003). O'Neill (2012O'Neill ( , 2016 found that such activities and training in the use of MT enable learners to write more accurately and receive higher subscores on L2 writing tasks (comprehensibility, spelling, content, and grammar) than those who did not.…”
Section: Limitations and Benefits Of Mtmentioning
confidence: 99%
“…Previous research in MT use has centered on analyzing structures that are especially vulnerable to translation errors and mistranslations (Dhakar, Sinha, & Pandey, 2013;Ghasemi & Hashemian, 2016), analyzing written texts by second language (L2) learners who used MT (Lee, 2019;Groves & Mundt, 2015), surveying learners' attitudes and use of MT (Im, 2017;Larson-Guenette, 2013;White & Heidrich, 2013), and searching for pedagogical applications and implementing translation tools in the context of teaching (Correa, 2014;Enkin & Mejías-Bikandi, 2016;Garcia & Pena, 2011). While much has been discussed about the educational implications of translation in L2 writing, it is not yet clear how exactly the learners use and integrate MT in their writing and whether individual learner differences such as proficiency level affect how learners use this online tool.…”
Section: Introductionmentioning
confidence: 99%
“…According to Vold (2018), Enkin and Mejías-Bikandi (2016), and Correa (2014), fomt can be used in foreign language classes as a way of raising language awareness with the guidance of a teacher. Learners should not be left to fend for themselves as best they can with the technology.…”
Section: Earlier Studies On Machine Translation Use In Foreign Language Writingmentioning
confidence: 99%